Monitoramento in-line da formação de nanocompósitos PP/MMT via intercalação no estado fundido - Bertolino, Marcelo Koga (2008)
The aim of this work is to monitor in-line, using an optical detector fitted at the extruder die exit, the formation of PP/MMT nanocomposites during polymer melt compounding. The intensity of the detector´s signal is dependent of the clay type (organofilization treatment), concentration and particle size, and so it is possible to monitor the presence of the clay tactoids due to their light extinction. The MMT clay is added as a pulse with constant weight into the PP extrusion flow and its presence is followed by the optical detector at the die exit. The data comes out as the common residence time distribution curves having its maximum intensity dependent upon the clay average particle size. On clay exfoliation the size of the tactoids are reduced to levels below the minimum particle size for producing light extinction and so the signal intensity reduces as the nanosize composite is formed. X-Ray diffraction analyses are used as offline monitoring of the nanocomposite formation. The results show that it is possible to use the optical detector to monitoring in-line the formation of nanocomposites.